Perilaku Informasi Masyarakat Duo Koto Malalo Terhadap Tradisi “Mambuka Kapalo Banda” Di Kanagarian Malalo Sumatera Barat Indonesia - Lailatur Rahmi; Johari Jamal (Bakaba, 2019)
The tradition of “mambuka Kapalo Banda” is one of knowledge culture in Kanagarian Malalo. “mambuka Kapalo Banda” is still being carried out because the indenous people stiil feel the venue and meaning captured from this tradition. The values taken from local knowledge have relevance to the planting of cultural values and Islamic values, so that this tradition needs to be continually managed and preserved by the local government. Instill the cultural values seen in this “mambuka kapalo Banda” in Malalo warrior.